Investigating the potential side effects of anti-TNF therapy for rheumatoid arthritis: cause for concern?. (April 2015) - Atzeni, Fabiola; Gianturco, Luigi; Talotta, Rossella; Varisco, Valentina; Ditto, Maria Chiara; Turiel, Maurizio; Sarzi-Puttini, Piercarlo
There are now five anti-TNF drugs available for clinical use, and it will not be long before they are joined by biosimilar drugs. Some patients treated with selective TNF drugs may develop adverse events such as infections, malignancies, acute infusion and injection reactions, autoimmunity and cardiovascular effects. Registry data consistently show that, particularly during the first 6 months, anti-TNF drugs slightly increase the risk of serious infections of the skin, soft tissues and joints, but it does not seem to increase the risk of cancer other than nonmelanoma skin cancers. A number of studies have shown that the administration of biological agents can lead to the formation of neutralizing and nonneutralizing antibodies. Lipid levels increase, but the atherogenic index remains stable and qualitative changes to lipid particles may reduce the risk of cardiovascular diseases. Patients treated with anti-TNF drugs therefore need to be monitored regularly.